2016
DOI: 10.4254/wjh.v8.i6.322
|View full text |Cite
|
Sign up to set email alerts
|

Burn injury induces histopathological changes and cell proliferation in liver of rats

Abstract: BI induces histopathological changes, upregulation of COX-2 immunoexpression, and cell proliferation in liver of rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
1
10
2
Order By: Relevance
“…Walker and Mason [ 6 ] used three different lengths of time – 3, 5 and 10 seconds – to obtain three types of injury depth. Two studies 14 , 16 used 3 seconds and observed a superficial (first degree) burn, which is consistent with the original study. Canhão et al 15 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Walker and Mason [ 6 ] used three different lengths of time – 3, 5 and 10 seconds – to obtain three types of injury depth. Two studies 14 , 16 used 3 seconds and observed a superficial (first degree) burn, which is consistent with the original study. Canhão et al 15 .…”
Section: Discussionsupporting
confidence: 77%
“…Walker and Mason 6 used 100°C as water temperature and 4 studies 18 , 19 , 22 , 25 did the same. More recent studies 16 , 17 , 23 used 90°C to 98°C as water temperatures, yet, the results were the same as those using 100°C; 2 studies [ 17 , 21 ] used 70°C to 78°C so as to obtain a more superficial injury; and 3 studies 14 , 15 , 17 used 80°C a 89°C and observed a median injury. The sum of the water temperature and the length of exposure time to the water are important to determine the degree of the injury.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the feasibility of megalocyte as a precancerous cell is not confirmed although the study of liver carcinogenesis in Wistar rats with a single dose of 7 mg/kg AFB 1 or subsequently repeated CCl 4 inhalation demonstrates that megalocytosis is the first observed lesion and the tumor cells usually located among the megalocytic cells [38]. In another aspect, polyploidy, which is usually found as megalocyte and binucleated cell, could also denote an adaptive mechanism to become more resistant to oxidative stress and genotoxic damage from xenobiotic [4, 14, 17, 28]. Several researchers elucidated that diploid hepatocytes enter the cell cycle faster than polyploid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some hepatocytes showed pyknotic nucleus or karyolysis. In context, Bortolin et al [23] recorded binucleation as consequence of cell injury followed by regenerative growth after injury [23] .…”
Section: Discussionmentioning
confidence: 99%